Endotyping COPD: hypoxia-inducible factor-2 as a molecular "switch" between the vascular and airway phenotypes?. (11th January 2023) - Myronenko, Oleh; Foris, Vasile; Crnkovic, Slaven; Olschewski, Andrea; Rocha, Sonia; Nicolls, Mark R.; Olschewski, Horst
COPD is a heterogeneous disease with multiple clinical phenotypes. COPD endotypes can be determined by different expressions of hypoxia-inducible factors (HIFs), which, in combination with individual susceptibility and environmental factors, may cause predominant airway or vascular changes in the lung. The pulmonary vascular phenotype is relatively rare among COPD patients and characterised by out-of-proportion pulmonary hypertension (PH) and low diffusing capacity of the lung for carbon monoxide, but only mild-to-moderate airway obstruction. Its histologic feature, severe remodelling of the small pulmonary arteries, can be mediated by HIF-2 overexpression in experimental PH models. HIF-2 is not only involved in the vascular remodelling but also in the parenchyma destruction. Endothelial cells from human emphysema lungs express reduced HIF-2α levels, and the deletion of pulmonary endothelial Hif-2 α leads to emphysema in mice. This means that both upregulation and downregulation of HIF-2 have adverse effects and that HIF-2 may represent a molecular "switch" between the development of the vascular and airway phenotypes in COPD. The mechanisms of HIF-2 dysregulation in the lung are only partly understood. HIF-2 levels may be controlled by NAD(P)H oxidases via iron- and redox-dependent mechanisms. A better understanding of these mechanisms may lead to the development of new therapeutic targets. Upregulation of endothelial HIF-2 may represent a new mechanism of the vascular phenotype in COPD, whereas downregulation of HIF-2 may cause damage of airways and lung parenchyma. HIF-2 may provide an important tool to achieve precision medicine in COPD. https://bit.ly/3UByVmR